Tolerability of calcitonin gene-related peptide monoclonal antibodies and other monoclonal antibodies in adults with concurrent migraine and other medical conditions - Kevin Weber; Tanner Ferderer; Meghan Hubert; Ann Pakalnis (SAGE Publishing, 2024)
Background/Hypothesis: Calcitonin gene-related peptide monoclonal antibodies (CGRP mabs) are relatively new preventive treatments in adult migraine. Co-morbid medical conditions such as autoimmune or other neurologic/oncologic disorders are not uncommon in migraine patients and some exhibit notable co-morbidity such as asthma. These clinical conditions may necessitate concomitant treatment with another monoclonal antibody with a different mechanism of action other than the CGRP pathway in some individuals with migraine. Methods: We report a retrospective case series in 23 patients identified from our headache clinic treated concurrently with a CGRP monoclonal antibody and other monoclonal antibody for another medical condition. These other medical conditions were neurologic, oncologic, or autoimmune conditions. These patients were evaluated for tolerability, safety, and stability of disease processes including their migraine response. Results/Conclusion: We did not find evidence of new adverse or serious adverse side effects with coadministration of CGRP and non-CGRP monoclonal antibodies during our study time period of 13 months, for the duration of overlap between treatments (between 3 and 12 months).